Gambaran Faktor-Faktor yang Mempengaruhi Kepatuhan Konsumsi Tablet Tambah Darah Pada Remaja Putri di Wilayah Kerja Puskesmas Narmada - Baiq Maulida Amani; Adli Putra Nugraha; Pratiwi Anggraini; Putu Cicilia Rarasati Kuta; Rizqina Alya Shafa (Malahayati Nursing Journal, 2026)
ABSTRACT Anemia in female adolescents remains a significant public health concern as it can impair cognitive concentration and lead to long-term health complications during pregnancy; although Iron-Folic Acid (IFA) supplementation programs have been implemented, consumption adherence remains suboptimal. This descriptive study aims to identify the factors influencing the adherence to IFA supplement consumption among 120 adolescent female respondents within the Narmada Public Health Center work area, selected using the Slovin formula. Data were collected via questionnaires covering IFA distribution, knowledge, attitudes, and practices (KAP), and subsequently analyzed using univariate analysis. The results revealed that while all respondents received IFA supplements from their schools (100%), only 64.2% consumed them according to the recommended guidelines. Furthermore, despite a high level of knowledge among the majority of respondents (97.5%), positive attitudes were only observed in 44.2%, and positive behavioral practices were recorded at 54.2%. Consequently, it can be concluded that while knowledge regarding anemia and IFA supplementation is generally good, consumption adherence remains low due to the prevalence of negative attitudes and behaviors; therefore, enhanced education, counseling, and strengthened school-based support are essential to optimize IFA supplement adherence. Keywords: Anemia, Iron-Folic Acid Supplementation, Adolescent Girls, Knowledge, Attitude, Practice. ABSTRAK Anemia pada remaja putri masih menjadi masalah kesehatan serius karena dapat mengganggu konsentrasi belajar dan berlanjut hingga kehamilan; meskipun program suplementasi Tablet Tambah Darah (TTD) telah dilaksanakan, namun kepatuhan konsumsi belum optimal. Penelitian deskriptif ini bertujuan untuk mengetahui gambaran faktor-faktor yang memengaruhi konsumsi TTD pada 120 responden remaja putri di wilayah kerja Puskesmas Narmada yang dipilih menggunakan rumus Slovin. Data dikumpulkan melalui kuesioner mengenai distribusi TTD, pengetahuan, sikap, serta perilaku, yang kemudian dianalisis secara univariat. Hasil penelitian menunjukkan bahwa seluruh responden menerima TTD dari sekolah (100%), namun hanya 64,2% yang mengonsumsinya sesuai anjuran; selain itu, mayoritas responden memiliki pengetahuan baik (97,5%), tetapi sikap positif hanya ditunjukkan oleh 44,2% responden dan perilaku positif tercatat pada 54,2% responden. Dapat disimpulkan bahwa pengetahuan remaja putri tentang anemia dan TTD tergolong baik, tetapi kepatuhan konsumsi masih rendah akibat dominasi sikap dan perilaku negatif, sehingga diperlukan peningkatan edukasi, pendampingan, dan dukungan sekolah agar kepatuhan konsumsi TTD dapat lebih optimal. Kata Kunci: Anemia, Tablet Tambah Darah, Remaja Putri, Pengetahuan, Sikap, Perilaku.